Prospects for the Development of Patriotism in Students in the Educational Process - Ismoilovich, Madaliev (Indonesian Journal Publisher, 2024)
This article highlights the thoughts of our ancestors about patriotic education and the development of patriotic qualities through artpedagogics using cora-events, modern approaches and various tools aimed at developing a sense of patriotism of young people in our country today.